Shear Strengthening with a Fiber-Reinforced Cementitious Matrix of Reinforced Concrete Elements Under Different Levels of Loads: An Experimental Investigation - Pavlo Vegera; Viktor Borzovic; Zinovii Blikharskyi; Iryna Grynyova; Jaroslav Baran (Construction Materials)
This article explores the impact of strengthening reinforced concrete beams under different load levels, focusing on the use of polyphenylene benzobisoxazole (P.B.O.) fibers in a stabilized inorganic matrix to enhance the shear capacity. This research examines the interaction between modern composite materials and existing reinforced concrete structures, highlighting the practical challenges when the full unloading of structures is impossible. The experiments demonstrate that strengthening significantly increases the shear strength, with a maximum enhancement of 25%. However, the effect decreases as the load applied during strengthening increases, dropping to 16% at 70% of the ultimate load. This research also highlights the importance of refining current calculation methods due to the complex stress–strain state of beams and the unpredictable nature of shear failures. It concludes that composite materials, especially fiber-reinforced cementitious matrix (FRCM) systems, provide a practical solution for enhancing structural performance while maintaining the integrity and safety of concrete elements. This article emphasizes that the strengthening efficiency should be adjusted based on the applied load, suggesting a 5% reduction in effectiveness for every 10% increase in the initial load level. The findings support the empirical hypothesis that the shear strength improvement diminishes linearly with higher load levels during strengthening.